DAG-LIKE SPERM DEFECT AND ACROSOME ABNORMALITIES INDICATING HEREDITARY SPERM DEFECTS IN A JERSEY BULL - SUNDARARAMAN, M N; GOPINATHAN, A; SUBRAMANIAN, A (The Indian Journal of Animal Reproduction, 2023)
A study was undertaken on the consistent occurrence of sperm abnormalities in a Jersey bull maintainedin an organized frozen semen production station. Data on semen collections and a representative ejaculatefrom the bull in question were collected to evaluate the semen characteristics. From the records it wasobserved that 74.5% of the ejaculates were rejected as fresh semen for poor semen quality especially in spermmorphology. The representative semen sample also revealed low sperm concentration, poor sperm motilityand sperm abnormalities up to 82.4%, of which 65.2% of the spermatozoa showed 'Dag-like' defect. Majorityof the spermatozoa in the ejaculate also showed abnormal acrosome status (75.1 %). Consistent occurrenceof high proportion of 'Dag-like' sperm defect and acrosome abnormalities suggested a genetic cause.
Keywords: Jersey bull; Dag-like sperm defect; Acrosorne defects; Genetic sperm defects